Comprehensive effects of lake dredging on microbial community and dissolved organic matter compositions in surface sediments - Hezhou Chen; Shaozhuang Guo; Songhe Zhang; Yongsheng Tang; Tilang Zhang; Xin Lv; Dejin Wang; Jicheng Zhong (Ecological Indicators)
Sediment dredging and submerged macrophyte restoration are effective ways to improve water quality, especially in eutrophic shallow lakes. However, the impact of dredging on the interactions between dissolved organic matter (DOM) and microbial communities in lake surface sediments remains unexplored, especially in areas planting submerged macrophytes. In this study, DOM composition and microbial community composition were explored by fluorescence spectrum-parallel factor analysis, Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS), and high-throughput sequencing during the transition from agricultural production lake to ecological lake. Results showed that dredging reduced dissolved organic carbon in surface sediments. Dredging had significantly higher effects than submerged macrophyte decomposition (SMD) on microbial community composition (especially micro-eukaryotic) and biomarkers in surface sediments. Dredging and SMD had more impacts on micro-eukaryotic community assembly than prokaryotic community. The co-occurrence network reveals that dredging and SMD reshaped the ecological relationships between micro-eukaryotes and prokaryotes in microbial food webs. Particularly, SMD damaged the microbial food web structure in surface sediments. FT-ICR-MS further reveals that the relative abundances of tannins and lignin in DOM were 76 % and 35 % higher in dredged areas than in non-dredged areas, respectively. DOM molecular compositions affected the micro-eukaryotic community more than the prokaryotic community. The Mantel test shows that dredging changed nutrients and DOM fluorescence components in sediments. The microbial community was closely related to the DOM molecular composition. This study highlights the importance of proper implementation of dredging combined with submerged macrophyte to restore eutrophic water bodies.